Treatment with intermittent PTH increases Wnt10b production by T cells in osteoporotic patients. Issue 12 (December 2015) - D'Amelio, P.; Sassi, F.; Buondonno, I.; Fornelli, G.; Spertino, E.; D'Amico, L.; Marchetti, M.; Lucchiari, M.; Roato, I.; Isaia, G.
Abstract Summary We evaluated the effect of parathyroid hormone (PTH) on Wnt10b production by immune system cells in humans. We showed that bone anabolic effect of intermittent PTH treatment may be amplified by T cells through increased production of Wnt10b. Chronic increase in PTH as in primary hyperparathyroidism does not increase Wnt10b expression. Introduction The aim of this study is to assess the effect of PTH on Wnt10b production by immune system cells in humans. We assessed both the effect of intermittent PTH administration (iPTH) and of chronic PTH hypersecretion in primary hyperparathyroidism (PHP). Methods Eighty-two women affected by post-menopausal osteoporosis were randomly assigned to treatment with calcium and vitamin D alone (22) or plus 1-84 PTH (42), or intravenous ibandronate (18). Wnt10b production by unfractioned blood nucleated cells and by T, B cells and monocytes was assessed by real-time RT-PCR and ELISA at baseline, 3, 6, 12 and 18 months of treatment. The effect of chronic elevation of PTH was evaluated in 20 patients affected by PHP at diagnosis and after surgical removal of parathyroid adenoma. WNT10b from both osteoporotic and PHP patients was compared to healthy subjects matched for age and sex. Results iPTH increases Wnt10b production by T cells, whereas PHP does not. After surgical restoration of normal parathyroid function, WNT10b decreases, although it is still comparable with healthy subjects' level. Thus, chronic elevation of PTH does not significantly increase WNT10b production as respect to control. Conclusions This is the first work showing the effect of both intermittent and chronic PTH increase on Wnt10b production by immune system cells. We suggest that, in humans, T cells amplified the anabolic effect of PTH on bone, by increasing Wnt10b production, which stimulates osteoblast activity.